2017
DOI: 10.1038/ncomms14792
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of Louisiana’s coastal wetlands to present-day rates of relative sea-level rise

Abstract: Coastal Louisiana has lost about 5,000 km2 of wetlands over the past century and concern exists whether remaining wetlands will persist while facing some of the world's highest rates of relative sea-level rise (RSLR). Here we analyse an unprecedented data set derived from 274 rod surface-elevation table-marker horizon stations, to determine present-day surface-elevation change, vertical accretion and shallow subsidence rates. Comparison of vertical accretion rates with RSLR rates at the land surface (present-d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
265
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(279 citation statements)
references
References 40 publications
9
265
5
Order By: Relevance
“…Rogers et al (2019) recently suggested that an increase in vertical accommodation space driven by RSLR may lead to increasing sedimentation and C sequestration; however, the limited tidal exchange and reduced sediment availability in this region may contradict this trend. Mean observed RSLR in this area is 9.5 mm/yr (AE6.33 mm/yr, n = 89; Jankowski et al 2017), which is 1.5 times higher than even the highest longer-term accretion rate we measured in this study, suggesting both created and natural marshes are at risk of drowning in SNWR. Our results support and augment these findings by demonstrating a substantial accretion deficit in created marshes in the western Chenier Plain, irrespective of environmental conditions or age.…”
Section: Created Marsh Persistencecontrasting
confidence: 52%
See 2 more Smart Citations
“…Rogers et al (2019) recently suggested that an increase in vertical accommodation space driven by RSLR may lead to increasing sedimentation and C sequestration; however, the limited tidal exchange and reduced sediment availability in this region may contradict this trend. Mean observed RSLR in this area is 9.5 mm/yr (AE6.33 mm/yr, n = 89; Jankowski et al 2017), which is 1.5 times higher than even the highest longer-term accretion rate we measured in this study, suggesting both created and natural marshes are at risk of drowning in SNWR. Our results support and augment these findings by demonstrating a substantial accretion deficit in created marshes in the western Chenier Plain, irrespective of environmental conditions or age.…”
Section: Created Marsh Persistencecontrasting
confidence: 52%
“…Aboveground litter from these species may therefore remain in the substrate for longer periods than S. alterniflora litter, which is readily decomposed (Lonard et al 2010(Lonard et al , 2013). Within the 13-and 32-yr-old marshes, however, stem density remained the most important predictor of LCAR, suggesting these marshes remain dependent upon autochthonous, rather than allochthonous contributions to sustain soil C accumulation rates (Jankowski et al 2017). That is, it floods at a depth and frequency that suppresses vegetative growth and decreases overall vertical accretion and organic C accumulation rates, which were 3.7 and 5.7 times lower than rates found in the 13-yr-old marsh.…”
Section: Role Of Vegetation and Environmental Factors In Accretion Anmentioning
confidence: 98%
See 1 more Smart Citation
“…Our results highlight the utility of the more plentiful mud load. While significant land loss in the Mississippi Delta is inevitable, accretion rates that persisted in the mud-dominated ACS for centuries (1-4 cm yr −1 ; Shen et al, 2015) may locally be sufficient to keep up with present-day rates of relative sea-level rise in the MD (1.3 ± 0.9 cm yr −1 ) (Jankowski et al, 2017) even after accounting for enhanced compaction due to sediment loading (Törnqvist et al, 2008). The goal of river diversions is to maximize their land building potential, which is determined by both sediment supply and SRE.…”
Section: Implications For Delta Evolution and Sustainabilitymentioning
confidence: 99%
“…On contrary, increased air temperature and CO 2 concentration can contribute to the marsh stability against sea-level rise. The fertilization effects of the increased air temperature and atmospheric CO 2 allow the coastal marshes to be more resilient against sea-level rise, but this study documents a sig- (Jankowski et al, 2017), the relative relationship between sediment supply and sea-level rise of different locations (Mariotti & Fagherazzi, 2010), and the availability of accommodation space (Schuerch et al, 2018) may provide more insights the spatial patterns of the area changes. Although the enhancement of plant growth from CO 2 , as discussed earlier, is mainly for C3 plants, the fertilization of CO 2 , based on a modeling study, can increase the marsh elevation for a mixed C3 and C4 plant community (by increasing plant production) in similar magnitude to the effect of increasing inorganic sediment input (Ratliff et al, 2015).…”
Section: The Marsh Area Changes In the Last 30 Yearsmentioning
confidence: 65%